Assessment of Pulmonary Function in Treated Pulmonary Tuberculosis Patients Using Spirometry - R. Anand; M. Thoupikka; Maria Lithi Rashmi; J. Sneha Joshi; M. Ananthi (The Journal of Association of Chest Physicians)
Background: Tuberculosis (TB) has significant long-term sequelae, especially pulmonary dysfunction, despite microbiological cure. This study assesses the demographic, nutritional, and spirometry profiles of patients with post-TB (PTB) sequelae in South India. Methods: A prospective observational study of 150 patients with PTB sequelae was conducted. Demographic details, smoking history, body mass index (BMI), and spirometry patterns were analyzed. Results: Of the 150 patients, 61.3% were male and 54.3% were smokers. Patients over 50 years of age formed the largest group (60.7%). BMI analysis revealed that 16.7% were underweight, 52.7% had normal weight, and 30.6% were overweight. Spirometry results showed normal patterns in 0.64%, obstructive patterns in 64%, restrictive patterns in 22%, and mixed ventilatory defects in 13.3%. Conclusion: PTB sequelae cause significant respiratory dysfunction, predominantly obstructive and restrictive types. Smoking and malnutrition are key contributors to these impairments, underscoring the need for targeted interventions, long-term follow-up, and structured rehabilitation programs.